2009
DOI: 10.1128/ec.00001-09
|View full text |Cite
|
Sign up to set email alerts
|

Iron Activates In Vivo DNA Binding of Schizosaccharomyces pombe Transcription Factor Fep1 through Its Amino-Terminal Region

Abstract: In Schizosaccharomyces pombe, the iron sensor Fep1 mediates the transcriptional repression of iron transport genes in response to high concentrations of iron. On the other hand, fep1؉ expression is downregulated under conditions of iron starvation by the CCAAT-binding factor Php4. In this study, we created a fep1⌬ php4⌬ double mutant strain where expression of fep1 ؉ was disengaged from its iron limitation-dependent repression by Php4 to examine the effects of iron on constitutively expressed functional fep1؉ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(68 citation statements)
references
References 41 publications
1
67
0
Order By: Relevance
“…Downstream of Grx4, the inactivation of Fep1 and activation of Php4 transcriptional repressors mediate the cellular response to iron deficiency (44). Briefly, when iron is experimentally depleted by the use of chelators, Fep1 is released from promoters of genes involved in iron uptake (45), whereas Php4 accumulates at the nucleus and represses transcription of genes coding for iron storage or iron-consuming proteins (46). Importantly enough, Grx4 is the real sensor of iron deprivation, probably through its ISC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Downstream of Grx4, the inactivation of Fep1 and activation of Php4 transcriptional repressors mediate the cellular response to iron deficiency (44). Briefly, when iron is experimentally depleted by the use of chelators, Fep1 is released from promoters of genes involved in iron uptake (45), whereas Php4 accumulates at the nucleus and represses transcription of genes coding for iron storage or iron-consuming proteins (46). Importantly enough, Grx4 is the real sensor of iron deprivation, probably through its ISC.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, upon low iron conditions Fep1 is released from promoters of genes involved in iron uptake, such as fio1 or str3 (Fig. 4, A and B) (45). As shown in Fig.…”
Section: Identification and Deletion Of The Gene Pfh1 Which Codes Fomentioning
confidence: 95%
“…Cell lysates were quantitated using the Bradford assay (47), and equal amounts of each sample were subjected to electrophoresis on 9% SDS-polyacrylamide gels. After electrophoresis, protein samples were electroblotted as described previously (9). The following primary antisera were used for immunodetection: monoclonal anti-GFP antibody (B-2; Santa Cruz Biotechnology) and monoclonal anti-PCNA antibody (PC10; Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…fip1 ϩ , fio1 ϩ , frp1 ϩ , and str1 ϩ /2 ϩ /3 ϩ ) and shuts down their expression to avoid deleterious consequences of iron overload (6,7). When iron levels are low, Fep1 is unable to bind DNA, resulting in the transcriptional induction of genes involved in iron acquisition (6,8,9). Analogous to S. pombe, other fungi use Fep1 orthologs to repress transcription of target genes in response to high iron.…”
mentioning
confidence: 99%
“…Labbé and his team took advantage of the Schiz. pombe model to identify the GATA-type transcription factor Fep1 [1][2][3] . The identification of Fep1 was significant because it revealed that iron-regulated gene expression in fungi other than S. cerevisiae is mediated by a group of non-canonical GATA-type transcription factors.…”
Section: Discovery Of Fep1 An Iron Sensor That Represses Iron Transpmentioning
confidence: 99%